Annotated Checklist of the Earthworms (Annelida: Clitellata: Megadrili) of Nepal - Singh, Ankit Kumar; Khanal, Laxman (Zootaxa, 2025)
This checklist of earthworms in Nepal was compiled from existing literature and documents 24 species across five families: Moniligastridae, Acanthodrilidae, Almidae, Lumbricidae, and Megascolecidae, found in various regions of the country. The family with the highest diversity is Megascolecidae, which includes nine species, followed by Lumbricidae with seven, and Acanthodrilidae with six species. Almidae and Moniligastridae each have one species represented. Four species—Drawida nepalensis, Eutyphoeus lippus, Eutyphoeus nepalensis, and Eutyphoeus pharpingianus—were first described taxonomically in Nepal and were considered endemic to the region. However, Drawida nepalensis, Eutyphoeus nepalensis, and Eutyphoeus pharpingianus have since been reported in other countries as well. Despite this documentation, Nepal remains underexplored in terms of earthworm diversity and lacks thorough taxonomic studies based on both morphology and molecular systematics. Therefore, this checklist serves as an important reference for future morphological and molecular taxonomic research on earthworms in Nepal.